Phytocenotic features of species of the genus Salsola L. (Chenopodiaceae Vent. / Amaranthaceae Juss.) in the desert part of the Syrdarya river valley - Osmonali, B.B.; Vesselova, P.V.; Kudabayeva, G.M.; Akhtayeva, N.Z. (Fundamental and Experimental Biology, 2022)
The study of species of the genus Salsola L. in the desert part of the Syrdarya river valley (Kyzylorda region) is of great importance for identifying the features of the structure of phytocenoses in this region, which will facilitate rational use of plant resources and make recommendations for the radical improvement and recultivation of pastures in this territory. Various phytocenoses are confined to this territory, including those with the participation (dominance) of species of the genus Salsola L. Classical botanical methods were used in the research process. Fundamental floral summaries were used to identify the collected material. Vegetation was studied applying traditional methods of field geobotanical research. According tothe results of the expedition work in the desert part of the Syrdarya river valley, 24 plant communities were described with the participation and dominance of species of the genus Salsola L. The communities differed from each other in the composition of the species. This is due to the diversity of the combination of environmental factors: natural physical and geographical and anthropogenic. The 24 communities represented can be divided into two groups: 1) communities dominated by species of the genus Salsola; 2) communities containing species of the genus Salsola. As a result, it was found that the annual species of the genus Salsola: S. nitraria, S. paulsenii and S. tragus are well adapted to the habitat conditions in the study area and can be used in reclamation work in desert zones.